Pengembangan Pendidikan Pesantren Perspektif Nurcholish Madjid - M. Munir (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2021)
The era of globalization has affected the lives of Indonesians, one of which is the educational aspect, especially in Islamic boarding schools. This can no longer be avoided by pesantren education institutions, especially if these educational institutions want to survive and succeed in the midst of globalization. Therefore, pesantren education institutions should carry out developments in their education, in order to realize efforts to respond and be responsive to the challenges of the times. Nurcholish Madjid is a Muslim scholar who discusses pesantren education in the modern era, with the idea of ​​modernizing pesantren education. The results of this study indicate that the development of pesantren education with the perspective of Nurcholish Madjid is a way, an effort to change better pesantren education, based on the modernization of Islamic boarding school education, in the sense that the development is carried out in a contemporary (modern) nuance, following the direction of the times, without eliminating the values ​​of authenticity of the pesantren itself (Indegenous), with the fields being developed including curriculum, learning methods and leadership. As for Nurcholish Madjid's thoughts, what can be adopted by education in general is Nurcholish Madjid's desire to create a curriculum that is balanced in emphasis, so that the principle of integrity is realized.